POTENSI BANGUNAN PARKIR SEBAGAI PEMBANGKIT LISTRIK TENAGA SURYA ATAP - I Gde Ari Biantara; Nyoman Satya Kumara; I. A. Dwi Giriantari (Jurnal SPEKTRUM, 2021)
Solar Power Plant (PLTS) is a renewable energy that converts sunlight into electricity.However, the construction of PLTS requires a large area of land so that for urban areas it is noteasy to get the required land. One of solution to this problem is to use the roof of the parkingbuilding as a rooftop solar power plant, the energy produced by the rooftop solar power plantcan be exported to the network because generally the energy demand for parking buildings isnot much. This paper discusses PLTS on the roof of parking buildings that have been built allover the world. The results of a review were obtained as many as 40 PLTS on the roof of theparking building which were built from 2010 to 2022 with a total capacity of 207,49 MW. ThisPLTS parking facility was built in the form of PLTS on the roof of the parking building, carportand parking canopy. Institutions that have built PLTS above their parking facilities includeairports, banks, malls, governments, water companies, recycling companies, pharmaceuticalcompanies, financial companies, car companies, hospitals, schools, stadiums and universities.